The ideational hegemonic gendered transactional ideology across ‘Long day’s journey into night’: a socio-semiotic analysis - Sara Samir El Daly (Insights into Language, Culture and Communication)
This study addresses the triangulation of language, power, and gender since it aims at examining the ideational function of language realized through the interpersonal profile. The interpersonal profile is investigated through the family relations and the literary discourse markers. The ideational meta-function is construed through the ideology-based value conducted through the experiential construal of the interpersonal relations between the characters of the play 'Long Day's Journey into Night' and the interpersonal metadiscourse devices of the authorship. This study employed both the quantitative and qualitative approaches. The corpus of the study was composed of the archived txt. files of the play and the qualitative interpretation of the conducted results. Analytically, the play corpus is the 43,209 thousand words. An integrated approach to investigate the ideational function is followed; it belongs to both the interpersonal metafunction (Halliday 2014) and the discourse marker (Hyland 2005). The results of the study classify the interpersonal profile into; firstly, the interpersonal identity-based practices realized and conducted through: the interactional meta-discourse devices' use, the propositional recurrences event model, the modalities dramatic ception, the co-joint masculine-based hegemony over the female-oriented activities, and the factive/fictive preceptory-oriented ideology. Secondly, the literary-style interpersonal realization is conducted through the characters'-cognitive complexity portrayal and the multiple ideological implications; the double-voice of the feminine discourse orients the 'herself's' interest and mitigates the interactions; the masculine's single voice discourse pattern is conducted for one-basic communicative end.   Received on: 22 December 2024 Accepted on: 19 January 2025 Published on: 15 February 2025